Co-creating and hosting PxP: a conference about patient engagement in research for and by patient partners - Dawn P. Richards; Hetty Mulhall; Joletta Belton; Savia de Souza; Trudy Flynn; Alex Haagaard; Linda Hunter; Amy Price; Sara Riggare; Janice Tufte; Rosie Twomey; Karim M. Khan (Research Involvement and Engagement)
Abstract Research projects, initiatives and conferences that include patients as partners rather than as participants are becoming more common. Including patients as partners (what we will call ‘patient partners’) is an approach called patient engagement or involvement in research, and we will call it patient engagement throughout this paper. Patient engagement moves traditional health research conferences and events to include a broader audience for their knowledge exchange and community building efforts, beyond academics and healthcare professionals. However, there are few examples of conferences where patients are given the opportunity to fully lead. Our conference went beyond patient engagement – it was patient-led. Patient partners conceived, planned, and decided on all aspects of a virtual conference. We present the work and processes we undertook throughout 2023 to create and produce a free conference called “PxP: For patients, by patients” or PxP for short, with a tagline of “Partnering to make research stronger.” PxP was patient-led and about patient engagement in research rather than a specific disease or condition. PxP was supported by the Canadian Institutes of Health Research Institute of Musculoskeletal Health and Arthritis. The PxP website, known as the PxP Hub, now houses the conference recordings along with resources about patient engagement in research. These resources were recommended by the PxP Steering Committee members, speakers, and others who attended the 2023 conference. Here we lead you through how the idea for PxP was generated; how the international patient partner Steering Committee was convened and supported; how PxP was brought to life over nine months; the PxP 3-day event and feedback collected to improve future efforts; trade-offs, challenges and learnings; and resources required to support this type of event. We close with what the future holds for PxP in 2024 and beyond. It’s time to elevate patients into leadership roles for conferences and events, and we encourage you to adopt the PxP ethos by using or adapting our approach and resources to support your opportunity.